2015
DOI: 10.1021/acs.jpcb.5b00825
|View full text |Cite
|
Sign up to set email alerts
|

Designing Nanoparticle Translocation through Cell Membranes by Varying Amphiphilic Polymer Coatings

Abstract: Nanoparticle-assisted drug delivery has been emerging as an active research area. Understanding and controlling the interaction of the coated-nanoparticles (NPs) with cell membranes is key to the development of the efficient drug delivery technologies and to the management of nanoparticle-related health and safety issues. Cellular uptake of nanoparticles coated with mixed hydrophilic/hydrophobic polymer ligands is known to be strongly influenced by the polymer pattern on the NP surface and remains open for fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 50 publications
1
82
0
Order By: Relevance
“…The standard values σ = 3.0 and γ = 4.5 are used in our study [Zhang et al , 2015; Zhang and Wang, 2015a; 2015b]. The mass, length and time scales are all normalized in the DPD simulations, with the unit of length taken to be the cutoff radius r c , the unit of mass to be that of the solvent beads, and the unit of energy to be k B T .…”
Section: Computational Model and Methodologymentioning
confidence: 99%
“…The standard values σ = 3.0 and γ = 4.5 are used in our study [Zhang et al , 2015; Zhang and Wang, 2015a; 2015b]. The mass, length and time scales are all normalized in the DPD simulations, with the unit of length taken to be the cutoff radius r c , the unit of mass to be that of the solvent beads, and the unit of energy to be k B T .…”
Section: Computational Model and Methodologymentioning
confidence: 99%
“…As illustrated in several studies, the size, shape, and surface functional groups of nanoparticles can significantly influence their behaviors in biological systems [12,13]. Our recent investigation revealed that silica and gold nanoparticles with bigger aspect ratios were taken up by cells in larger amounts and had greater impact on gene transfection performance [14,15].…”
Section: Introductionmentioning
confidence: 90%
“…Mishra et al showed that human immunodeficiency virus (HIV) transactivator (TAT) peptide conjugated to a small cargo can easily translocate through the membrane via forming a membrane pore, but if the cargo is of a few nanometer size more, then it will bind to the cell membrane and eventually get internalized via the endocytic pathway [25]. In order to develop GTs following non-endocytic pathway, certain criteria have to be followed such as large size, amphiphilicity, and anionic nature [26,27,28,29]. Above all, it is quite necessary to study the non-endocytic pathway in more detail and it is possible by using computational tools, fluorescent probes, and cut through techniques to know the in depth nature of the cell membrane penetration of GTs.…”
Section: Mechanism For Effective Release Of Exogenous Nucleic Acidmentioning
confidence: 99%